FACTORS AFFECTING OUTCOME OF PATIENTS WITH MULTIPLE MYELOMA - Basit, Abdul; Siddiqui, Neelam; Hameed, Abdul; Muzaffar, Narjis; Athar, Sohail (Journal of Ayub Medical College Abbottabad, 2014)
Background: Multiple myeloma is a heterogeneous disease, with wide survival range and multiple risk factors and staging systems linked to survival. The objective of this study was to assess the overall survival of patients with multiple myeloma (MM) diagnosed and treated at Shaukat Khanum Memorial Cancer Hospital (SKMCH), Lahore with respect to various prognostic factors. Methods: This was a survival analysis with data collected retrospectively on 82 patients fulfilling the diagnostic criteria of multiple myeloma. Overall survival was studied in relation to International Staging System (ISS), renal failure (Serum creatinine >2 mg/dl), anaemia (Hemoglobin <10 mg/dl), bone involvement (presence of lytic lesion on skeletal survey) and hypercalcemia (serum calcium >11mg/dl) due to multiple myeloma at the time of diagnosis. Results: Mean age of patients was 61 years, including 67% males and 33% females. Median overall survival for ISS stage-I (24%), stage-II (44%) and stage-III (32%) was 58, 41 and 12 months respectively (p=0.01). Patients with renal impairment (16% of total) had median overall survival of 13 months compared to 41 months in patients without renal involvement (p=0.02). Hypercalcemia was noted in 27% patients with median overall survival of 32 months versus 38 months in patients without hypercalcemia, but its impact on survival was statistically insignificant (p=0.79). Similarly no significant impact on survival was noted in patients with bone involvement or anaemia found in 74 % and 38% of patient's respectively. Conclusions: ISS stage and renal failure due to multiple myeloma at presentation have a significant impact on survival. However, other prognostic factors like bone involvement, anaemia and hypercalcemia were not shown to influence survival significantly. Keywords: Multiplemyeloma, survival, anaemia, hypercalcemia